Characterization of Poultry Gelatins Prepared by a Biotechnological Method for Targeted Changes at the Molecular Level - Prokopová, Aneta; Mokrejš, Pavel; Gál, Robert; Pavlačková, Jana; Hurajová, Anna (International journal of molecular sciences, 2024)
Chicken collagen is a promising raw material source for the production gelatins and hydrolysates. These can be prepared biotechnologically using proteolytic enzymes. By choosing the appropriate process conditions, such changes can be achieved at the molecular level of collagen, making it possible to prepare gelatins with targeted properties for advanced cosmetic, pharmaceutical, medical, or food applications. The present research aims to investigate model samples of chicken gelatins, focusing on: (i) antioxidant activity using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2-azinobis-3-etylbenzotiazolin-6-sulfonic acid (ABTS); (ii) the distribution of molecular weights via gel permeation chromatography with refractometric detection (GPC-RID); (iii) functional groups and the configuration of polypeptide chains related to molecular-level properties using Fourier transform infrared spectroscopy (FTIR); (iv) the microbiological populations on sabouraud dextrose agar (SDA), plate count agar (PCA), tryptic soy agar (TSA), and violet red bile lactose (VRBL) using the matrix-assisted laser desorption ionization (MALDI) method. Antioxidant activity towards ABTS radicals was more than 80%; activity towards DPPH radicals was more than 69%. The molecular weights of all gelatin samples showed typical α-, β-, and γ-chains. FTIR analysis confirmed that chicken gelatins all contain typical vibrational regions for collagen cleavage products, Amides A and B, and Amides I, II, and III, at characteristic wavenumbers. A microbiological analysis of the prepared samples showed no undesirable bacteria that would limit advanced applications of the prepared products. Chicken gelatins represent a promising alternative to products made from standard collagen tissues of terrestrial animals.
Keywords: amidy; Agar; kur domácí; Collagen; kolagen; Antioxidants; molecular weight; functional groups; Sulfonic Acids; drůbež; benzothiazoly; kyseliny sulfonové; Chickens; antioxidant activity; biotechnology; Animals; gelatin; microbial population; Biphenyl Compounds; antioxidancia; zvířata; želatina; Amides; agar; Poultry; Benzothiazoles; bifenylové sloučeniny; Gelatin